2021
DOI: 10.1155/2021/7031178
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes of Sensorimotor Resting-State Functional Connectivity Differentiate between Patients with Thalamic Infarction and Pontine Infarction

Abstract: Purpose. We investigated the disparate influence of lesion location on functional damage and reorganization of the sensorimotor brain network in patients with thalamic infarction and pontine infarction. Methods. Fourteen patients with unilateral infarction of the thalamus and 14 patients with unilateral infarction of the pons underwent longitudinal fMRI measurements and motor functional assessment five times during a 6-month period (<7 days, at 2 weeks, 1 month, 3 months, and 6 months after stroke onset). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This is in line with our findings of decreased inter-domain connectivity. 43 Previous literature already has shown differences in dynamic functional connectivity of different phases post stroke 18 or lesion location 47 which is consistent with our differences in findings. The highly intra-domain connected state was previously reported to be associated with enhanced levels of brain plasticity 48 and could indicate the recovery process of the brain in the subacute phase post-stroke.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with our findings of decreased inter-domain connectivity. 43 Previous literature already has shown differences in dynamic functional connectivity of different phases post stroke 18 or lesion location 47 which is consistent with our differences in findings. The highly intra-domain connected state was previously reported to be associated with enhanced levels of brain plasticity 48 and could indicate the recovery process of the brain in the subacute phase post-stroke.…”
Section: Discussionsupporting
confidence: 92%
“…Although the enhanced activation of the contralateral brain region after stroke can promote functional rehabilitation in the short term, it could also cause wrong movement patterns such as associated movement, which has adverse effects on the rehabilitation of the neurological function of the damaged hemisphere ( 33 ). The better the prognosis for rehabilitation, the more the degree of abnormal hyperactivation of the healthy hemisphere is reduced during rehabilitation and the more normalized the imbalance in bilateral brain function due to lesion injury ( 26 , 34 ). In this study, some brain regions in the unaffected hemisphere showed enhanced functional connectivity, while the functional connectivity between the left basal ganglia, left temporal lobe, and left marginal lobe was weakened after scalp acupuncture treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ye et al, 2022;Chen Ye et al, 2022]. Advanced neuroimaging techniques, such as functional magnetic resonance imaging (fMRI) [Bonkhoff et al, 2020[Bonkhoff et al, , 2021He et al, 2021;Salvalaggio et al, 2020;Wang et al, 2021], diffusion tensor imaging (DTI) [Chen et al, 2019;Jang et al, 2019;Nemati et al, 2022] and positron emission tomography (PET) [Dieterich et al, 2005;Dieterich & Brandt, 2008;Kopelman, 2015;Rudolphi-Solero et al, 2022;Stenset et al, 2007;Weder et al, 1994;Willoch et al, 2004], have made important contributions to our understanding of these mechanisms. Thalamic infarction can lead to structural and functional changes in the brain, including altered white matter integrity [Chuo Li, 2011;Krause et al, 2012], cortical reorganization [He et al, 2021;Krause et al, 2014;Wang et al, 2021], and even brain network dysfunction [Favaretto et al, 2022;He et al, 2021;Hosomi et al, 2015;Wang et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced neuroimaging techniques, such as functional magnetic resonance imaging (fMRI) [Bonkhoff et al, 2020[Bonkhoff et al, , 2021He et al, 2021;Salvalaggio et al, 2020;Wang et al, 2021], diffusion tensor imaging (DTI) [Chen et al, 2019;Jang et al, 2019;Nemati et al, 2022] and positron emission tomography (PET) [Dieterich et al, 2005;Dieterich & Brandt, 2008;Kopelman, 2015;Rudolphi-Solero et al, 2022;Stenset et al, 2007;Weder et al, 1994;Willoch et al, 2004], have made important contributions to our understanding of these mechanisms. Thalamic infarction can lead to structural and functional changes in the brain, including altered white matter integrity [Chuo Li, 2011;Krause et al, 2012], cortical reorganization [He et al, 2021;Krause et al, 2014;Wang et al, 2021], and even brain network dysfunction [Favaretto et al, 2022;He et al, 2021;Hosomi et al, 2015;Wang et al, 2021]. These changes can affect both adjacent and distant brain regions, such as the basal ganglia (motor pathways) [Favaretto et al, 2022;Wang et al, 2021], prefrontal cortex [Krause et al, 2014], sensory pathways [He et al, 2021;Wang et al, 2021] and even vision pathways [Holly Bridge, 2011;Millington et al, 2014;Chen Ye et al, 2022], all of which may result in a wide range of clinical symptoms following thalamic infarction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation